High-fluidity PA66 material and preparation method thereof
By using snowflake flake ceramic particles in PA66 materials, interfering with hydrogen bonding and affecting crystallization behavior, the problem of insufficient fluidity of traditional PA66 materials is solved, the preparation of high-flow PA66 materials is achieved, and the efficiency of injection molding is improved.
Patent Information
- Application Number
- CN202411679872.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Traditional PA66 materials have limitations in terms of fluidity and are difficult to fill complex mold cavity, resulting in a long injection molding cycle and affecting production efficiency.
Snowflake-shaped ceramic particles are used as fillers to reduce viscosity by interfering with the hydrogen bonding between PA66/PA12T copolymer molecules, and affect the crystallization behavior of PA66, reducing the crystallinity, thereby improving the fluidity of PA66.
It effectively improves the fluidity of PA66 material, reduces the crystallinity, improves the motility of the molecular chain, and promotes the efficiency of injection molding.
Smart Images

Figure BDA0005148040550000051 
Figure BDA0005148040550000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of functional materials, and in particular to a high-fluidity PA66 material and a preparation method thereof. Background Art
[0002] PA66 is polyhexamethylene adipamide, and its molecular chain is synthesized by polycondensation of adipic acid and hexamethylenediamine. The amide bond (-CONH-) in the chemical structure makes PA66 have certain crystallinity and good mechanical properties. It has high strength, rigidity and wear resistance, and is widely used in the field of engineering plastics. For example, it is used to manufacture engine parts and interior parts in automobile manufacturing; it is used to manufacture connectors in the field of electronic appliances. However, conventional PA66 has certain limitations in terms of fluidity. In modern manufacturing, with the increasing complexity of product design, the demand for plastic materials that can form thin-walled and fine structural parts is increasing. Traditional PA66 is often difficult to fill the mold cavity when injection molding these complex parts due to its general fluidity. For example, some tiny parts in precision electronic equipment, such as micro gears, require materials with high fluidity to ensure complete molding. In the process of large-scale production, the injection molding cycle has an important impact on production efficiency. The low fluidity of PA66 will lead to slow filling speed during injection molding, thereby increasing the molding cycle. In order to improve production efficiency and reduce production costs, research and development of high-fluidity PA66 materials is an urgent problem to be solved. Summary of the invention
[0003] Technical problem to be solved: The purpose of the present invention is to provide a high-fluidity PA66 material and a preparation method thereof, using snowflake-shaped flaky ceramic particles as fillers. The snowflake-shaped flaky ceramic particles are composed of a porous TiO2 film and hexagonal crystal zinc oxide, and have a needle-shaped porous structure, such as flaky snowflakes, which can interfere with the hydrogen bonding between PA66 / PA12T copolymer molecules, thereby reducing viscosity. At the same time, it can also affect the crystallization behavior of PA66, thereby helping to reduce the degree of crystallinity. The larger the size of the crystals in PA66, the more perfect the degree of crystallization, and the lower the mobility of its molecular chain. The addition of snowflake-shaped flaky ceramic particles can effectively reduce the degree of crystallinity of PA66 and improve the mobility of the molecular chain, thereby improving the fluidity of PA66.
[0004] Technical solution: A high-fluidity PA66 material, comprising the following components, by weight: 100 parts of PA66 particles, 4-5 parts of PA12T, 5-20 parts of snowflake-shaped ceramic particles, 10980.4 parts of antioxidants, and 1 part of silicone. Furthermore, the thickness of the snowflake-shaped ceramic particles is 1-2 μm, and the porosity is 70-86%. Furthermore, the preparation method of the snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, and let stand for degassing to obtain a spinning solution; Step 2: Performing electrospinning using an electrospinning device to obtain an electrospinning membrane; Step 3: placing the electrospun membrane in a muffle furnace, heating the temperature to 700°C at a rate of 1.5°C / min, and keeping the temperature for 5-8h to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 3-6 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120°C for 8-12 hours; Step 8: Cooling, washing the product with water 3-5 times and then drying; Step 9: Place in a muffle furnace, treat at 700° C. in an air atmosphere for 1-2 hours, take out, and cool to obtain snowflake-shaped ceramic particles. Further, the Mw of the polyvinyl pyrrolidone is 1,300,000. Furthermore, the volume ratio of ethanol to acetic acid is 4:1. Furthermore, the electrospinning conditions are as follows: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 20-24 kV, and the receiving distance from the receiving plate is 14-16 cm. The preparation method of the above-mentioned high-fluidity PA66 material is as follows: S1: Take PA66 particles and PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill it with CO2 until the pressure reaches 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210°C below the reactor, 220°C in the reactor, and 200°C above the reactor, and then the pressure is maintained for 1-2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 270-280°C, and keep it warm for 1 hour to obtain the copolymer; S4: placing the copolymer in a digital temperature-controlled electric heating mantle at 80°C, heating for 2 h, adding the snowflake-shaped ceramic particles, and stirring for 2 h; S5: adding antioxidant 1098 and silicone, and continuing to stir for 1 h to obtain a mixture; S6: using a twin-screw extruder to feed the mixed material, extruding and granulating, and obtaining pellets; S7: Dry the pellets and perform injection molding using an injection molding machine to obtain a high-fluidity PA66 material. Furthermore, in the S6, the extrusion granulation temperature is 260-290° C., and the screw speed is 500-550 rpm. Furthermore, in S7, the injection temperature is 280-300°C, the injection pressure is 50-70MPa, and the mold temperature is 100-140°C. Beneficial effects: 1. The present invention adopts snowflake-shaped ceramic particles as fillers. The snowflake-shaped ceramic particles are composed of porous TiO2 membrane and hexagonal structured zinc oxide crystals, and have a needle-shaped porous structure, such as flake snowflakes, which can interfere with the hydrogen bonding between PA66 / PA12T copolymer molecules, thereby reducing viscosity and improving the fluidity of the material. 2. The addition of snowflake-shaped ceramic particles in the present invention can also affect the crystallization behavior of PA66, thereby helping to reduce the degree of crystallinity. The larger the size of the crystals in PA66, the more perfect the degree of crystallization, and the lower the mobility of its molecular chain. The addition of snowflake-shaped ceramic particles can effectively reduce the crystallinity of PA66 and improve the mobility of the molecular chain, thereby improving the fluidity of PA66. 3. The present invention also copolymerizes PA66 and PA12T. PA12T is a long-chain alkyl polyamide, whose molecular chain is inserted between the molecular chains of PA66, interfering with its normal crystallization process, thereby reducing the viscosity of the copolymer and improving its fluidity. DETAILED DESCRIPTION Example 1 The preparation method of snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone with a Mw of 1300000 and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 4:1, and stand for degassing to obtain a spinning solution; Step 2: Perform electrospinning using an electrospinning device, the electrospinning conditions are: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 20 kV, and the receiving distance from the receiving plate is 14 cm, to obtain an electrospinning membrane; Step 3: placing the electrospun membrane in a muffle furnace, heating the temperature to 700°C at a rate of 1.5°C / min, and keeping the temperature for 7 hours to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 5 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120° C. for 10 hours; Step 8: Cooling, washing the product with water 4 times and then drying; Step 9: Place in a muffle furnace, treat at 700°C in an air atmosphere for 2 hours, take out, and cool to obtain snowflake-shaped ceramic particles with a thickness of 1.65 μm. Example 2 The preparation method of snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone with a Mw of 1300000 and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 4:1, and stand for degassing to obtain a spinning solution; Step 2: Perform electrospinning using an electrospinning device, the electrospinning conditions are: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 22 kV, and the receiving distance from the receiving plate is 15 cm, to obtain an electrospinning membrane; Step 3: placing the electrospun membrane in a muffle furnace, heating the temperature to 700°C at a rate of 1.5°C / min, and keeping the temperature for 7 hours to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 5 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120°C for 10 hours; Step 8: Cooling, washing the product with water 4 times and then drying; Step 9: Place in a muffle furnace, treat at 700°C in an air atmosphere for 2 hours, take out, and cool to obtain snowflake-shaped ceramic particles with a thickness of 1.63 μm. Example 3 The preparation method of snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone with a Mw of 1300000 and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 4:1, and stand for degassing to obtain a spinning solution; Step 2: Perform electrospinning using an electrospinning device, the electrospinning conditions are: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 24 kV, and the receiving distance from the receiving plate is 16 cm, to obtain an electrospinning membrane; Step 3: placing the electrospun membrane in a muffle furnace, heating the temperature to 700°C at a rate of 1.5°C / min, and keeping the temperature for 7 hours to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 5 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120°C for 10 hours; Step 8: Cooling, washing the product with water 4 times and then drying; Step 9: Place in a muffle furnace, treat at 700°C in an air atmosphere for 2 hours, take out, and cool to obtain snowflake-shaped ceramic particles with a thickness of 1.85 μm. Example 4 The preparation method of snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone with a Mw of 1300000 and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 4:1, and stand for degassing to obtain a spinning solution; Step 2: Perform electrospinning using an electrospinning device, the electrospinning conditions are: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 22 kV, and the receiving distance from the receiving plate is 15 cm, to obtain an electrospinning membrane; Step 3: placing the electrospun membrane in a muffle furnace, heating the temperature to 700°C at a rate of 1.5°C / min, and keeping the temperature for 7 hours to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 3 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120°C for 10 hours; Step 8: Cooling, washing the product with water 4 times and then drying; Step 9: Place in a muffle furnace, treat at 700°C in an air atmosphere for 2 hours, take out, and cool to obtain snowflake-shaped ceramic particles with a thickness of 1.70 μm. Example 5 The preparation method of snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone with a Mw of 1300000 and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, the volume ratio of ethanol to acetic acid is 4:1, and stand for degassing to obtain a spinning solution; Step 2: Perform electrospinning using an electrospinning device, the electrospinning conditions are: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 22 kV, and the receiving distance from the receiving plate is 15 cm, to obtain an electrospinning membrane; Step 3: placing the electrospun membrane in a muffle furnace, heating the temperature to 700°C at a rate of 1.5°C / min, and keeping the temperature for 7 hours to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 6 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120°C for 10 hours; Step 8: Cooling, washing the product with water 4 times and then drying; Step 9: Place in a muffle furnace, treat at 700°C in an air atmosphere for 2 hours, take out, and cool to obtain snowflake-shaped ceramic particles with a thickness of 1-2 μm. The average particle size and porosity of the snowflake-shaped ceramic particles were measured. The results are shown in Table 1: Table 1 The snowflake-shaped ceramic particles prepared in Example 2 were selected for subsequent experiments. Example 6 A method for preparing a high-fluidity PA66 material, characterized in that: the preparation method is as follows: S1: Take 100 parts of PA66 particles and 4 parts of PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill it with CO2 until the pressure is 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210°C below the reactor, 220°C in the reactor, and 200°C above the reactor, and then the pressure is maintained for 2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 275°C, and keep it warm for 1 hour to obtain the copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80°C, heat for 2 h, add 15 parts of snowflake-shaped ceramic particles, and stir for 2 h; S5: Add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 hour to obtain a mixture; S6: feeding the mixed material into a twin-screw extruder, extruding and granulating, the extrusion and granulation temperature is 280° C., the screw speed is 550 rpm, and granules are obtained; S7: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C., thereby obtaining a high-fluidity PA66 material. Example 7 A method for preparing a high-fluidity PA66 material, characterized in that the preparation method is as follows: S1: Take 100 parts of PA66 particles and 5 parts of PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill CO2 to a pressure of 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210℃ below the reactor, 220℃ in the reactor, and 200℃ above the reactor, and then the pressure is maintained for 2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 275℃, and keep it warm for 1 hour to obtain the copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80 °C, heat for 2 h, then add 15 parts of snowflake-shaped ceramic particles and stir for 2 h; S5: Add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 hour to obtain a mixture; S6: feeding the mixed material into a twin-screw extruder, extruding and granulating, the extrusion and granulation temperature is 280° C., the screw speed is 550 rpm, and granules are obtained; S7: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C., thereby obtaining a high-fluidity PA66 material. Example 8 A method for preparing a high-fluidity PA66 material, characterized in that the preparation method is as follows: S1: Take 100 parts of PA66 particles and 5 parts of PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill CO2 to a pressure of 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210℃ below the reactor, 220℃ in the reactor, and 200℃ above the reactor, and then the pressure is maintained for 2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 275℃, and keep it warm for 1 hour to obtain the copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80 °C, heat for 2 h, then add 5 parts of snowflake-shaped ceramic particles and stir for 2 h; S5: Add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 hour to obtain a mixture; S6: feeding the mixed material into a twin-screw extruder, extruding and granulating, the extrusion and granulation temperature is 280° C., the screw speed is 550 rpm, and granules are obtained; S7: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C., thereby obtaining a high-fluidity PA66 material. Example 9 A method for preparing a high-fluidity PA66 material, characterized in that the preparation method is as follows: S1: Take 100 parts of PA66 particles and 5 parts of PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill CO2 to a pressure of 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210℃ below the reactor, 220℃ in the reactor, and 200℃ above the reactor, and then the pressure is maintained for 2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 275℃, and keep it warm for 1 hour to obtain the copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80 °C, heat for 2 h, then add 10 parts of snowflake-shaped ceramic particles and stir for 2 h; S5: Add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 hour to obtain a mixture; S6: feeding the mixed material into a twin-screw extruder, extruding and granulating, the extrusion and granulation temperature is 280° C., the screw speed is 550 rpm, and granules are obtained; S7: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C., thereby obtaining a high-fluidity PA66 material. Example 10 A method for preparing a high-fluidity PA66 material, characterized in that the preparation method is as follows: S1: Take 100 parts of PA66 particles and 5 parts of PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill CO2 to a pressure of 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210℃ below the reactor, 220℃ in the reactor, and 200℃ above the reactor, and then the pressure is maintained for 2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 275℃, and keep it warm for 1 hour to obtain the copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80 °C, heat for 2 h, then add 20 parts of snowflake-shaped ceramic particles and stir for 2 h; S5: Add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 hour to obtain a mixture; S6: feeding the mixed material into a twin-screw extruder, extruding and granulating, the extrusion and granulation temperature is 280° C., the screw speed is 550 rpm, and granules are obtained; S7: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C., thereby obtaining a high-fluidity PA66 material. Comparative Example 1 The difference between this embodiment and embodiment 7 is that PA12T is not added. Specifically: A method for preparing a high-fluidity PA66 material, characterized in that the preparation method is as follows: S1: Take 100 parts of PA66 particles and place them in a digital temperature-controlled electric heating mantle at 80°C. After heating for 2 h, add 15 parts of snowflake-shaped ceramic particles and stir for 2 h. S2: Add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 hour to obtain a mixture; S3: using a twin-screw extruder to feed the mixed material, extruding and granulating, the extrusion granulation temperature is 280°C, the screw speed is 550 rpm, and granules are obtained; S4: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C. to obtain a high-fluidity PA66 material. Comparative Example 2 The difference between this embodiment and embodiment 7 is that no snowflake-shaped ceramic particles are added. Specifically: A method for preparing a high-fluidity PA66 material, characterized in that the preparation method is as follows: S1: Take 100 parts of PA66 particles and 5 parts of PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill CO2 to a pressure of 0.3MPa; S2: The reactor adopts a three-stage heating method, and the temperature is raised to 210℃ below the reactor, 220℃ in the reactor, and 200℃ above the reactor, and then the pressure is maintained for 2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 275℃, and keep it warm for 1 hour to obtain the copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80°C, add 0.4 parts of antioxidant 1098 and 1 part of silicone, and continue stirring for 1 h to obtain a mixture; S5: using a twin-screw extruder to feed the mixed material, extruding and granulating, the extrusion granulation temperature is 280°C, the screw speed is 550 rpm, and granules are obtained; S6: Dry the pellets and perform injection molding using an injection molding machine. The injection molding temperature is 290° C., the injection molding pressure is 60 MPa, and the mold temperature is 130° C., thereby obtaining a high-fluidity PA66 material. With reference to national standards, various properties of the high-fluidity PA66 materials prepared in various embodiments were tested, including melting point, viscosity, melt flow rate and tensile strength; the test results are shown in Table 2 below: Table 2 The above embodiments are intended to provide a clear and complete description of the technical solution, and are partial implementations of the present invention, rather than all implementations. However, the implementations of the present invention are not limited to the above embodiments, and any other changes, modifications, substitutions, combinations or simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.
Claims
1. A high-fluidity PA66 material, characterized by: The invention comprises the following ingredients in parts by weight: 100 parts of PA66 particles, 4-5 parts of PA12T, 5-20 parts of snowflake-shaped ceramic particles, 10980.4 parts of antioxidant and 1 part of silicone.
2. A high-fluidity PA66 material according to claim 1, characterized in that: The thickness of the snowflake-shaped ceramic particles is 1-2 μm, and the porosity is 70-86%.
3. The high-fluidity PA66 material according to claim 1, characterized in that: The preparation method of the snowflake-shaped ceramic particles is as follows: Step 1: Take 4 parts of polyvinyl pyrrolidone and 20 parts of tetrabutyl titanate, dissolve them in a mixed solvent of 100 parts of ethanol and acetic acid, and let stand for degassing to obtain a spinning solution; Step 2: Performing electrospinning using an electrospinning device to obtain an electrospinning membrane; Step 3: Place the electrospun membrane in a muffle furnace, heat it to 700°C at a rate of 1.5°C / min, and keep it warm for 5-8h to obtain a TiO2 membrane; Step 4: crushing to obtain TiO2 film particles; Step 5: Take 3 parts of zinc acetate and 4 parts of PEG20000, add 150 parts of water, and stir until completely dissolved; Step 6: Add 3-6 parts of NaOH, stir to dissolve, and place the solution in a hydrothermal kettle; Step 7: Immerse the TiO2 film particles in the solution in the hydrothermal kettle, seal the hydrothermal kettle, and keep it at 120°C for 8-12 hours; Step 8: Cooling, washing the product with water 3-5 times and then drying; Step 9: Place in a muffle furnace, treat at 700°C in an air atmosphere for 1-2 hours, take out, and cool to obtain snowflake-shaped ceramic particles.
4. A high-fluidity PA66 material according to claim 3, characterized in that: The Mw of the polyvinyl pyrrolidone is 1,300,000.
5. The high-fluidity PA66 material according to claim 3, characterized in that: The volume ratio of the ethanol to the acetic acid is 4:
1.
6. The high-fluidity PA66 material according to claim 3, characterized in that: The electrospinning conditions are as follows: the inner diameter of the syringe needle is 0.3 mm, the outer diameter is 0.55 mm, the spinning voltage is 20-24 kV, and the receiving distance from the receiving plate is 14-16 cm.
7. A method for preparing a high-fluidity PA66 material according to any one of claims 1 to 6, characterized in that: The preparation method is as follows: S1: Take PA66 particles and PA12T, add them into the reactor, seal the polymerization reactor, replace the air in the reactor with CO2, and fill it with CO2 until the pressure reaches 0.3MPa; S2: The reactor adopts a three-stage heating method, with the temperature rising to 210℃ below the reactor, 220℃ in the reactor, and 200℃ above the reactor, and then maintaining the pressure for 1-2 hours; S3: Slowly release the gas to release the water vapor in the reactor, raise the temperature to 270-280°C, and keep the temperature for 1 hour to obtain a copolymer; S4: Place the copolymer in a digital temperature-controlled electric heating mantle at 80°C, heat for 2 h, then add the snowflake-shaped ceramic particles and stir for 2 h; S5: adding antioxidant 1098 and silicone, and continuing stirring for 1 hour to obtain a mixture; S6: using a twin-screw extruder to feed the mixed material, extruding and granulating, and obtaining pellets; S7: Dry the pellets and perform injection molding using an injection molding machine to obtain a high-fluidity PA66 material.
8. The method for preparing a high-fluidity PA66 material according to claim 7, characterized in that: The extrusion granulation temperature in S6 is 260-290° C., and the screw speed is 500-550 rpm.
9. The method for preparing a high-fluidity PA66 material according to claim 7, characterized in that: In the S7, the injection temperature is 280-300°C, the injection pressure is 50-70MPa, and the mold temperature is 100-140°C.